Continued Decline in Obesity and Severe Obesity Prevalence Among New York City Public School Youth in Grades K‐8: 2011‐2017. Issue 3 (24th February 2020) - Day, Sophia E.; D'Agostino, Emily M.; Huang, Terry T.‐K.; Larkin, Michael; Harr, Lindsey; Konty, Kevin J.
Abstract : Objective: This study aimed to estimate population‐level prevalence of obesity and severe obesity for New York City youth and examine the most recent trends over time. Methods: All public school youth in grades kindergarten through eighth (K‐8) (2011‐2012 through 2016‐2017) with valid weight and height measures were included ( N  = 1, 137, 782 unique students; 3, 720, 297 observations). Age‐ and sex‐specific BMI percentiles for obesity and severe obesity were estimated using Centers for Disease Control and Prevention growth charts. Repeated cross‐sectional analyses were conducted using logistic regression, weighting for missing or invalid responses and accounting for clustering by students and schools to examine trends over time and by sociodemographics. Results: Among youth in K‐8 (aged 5‐15 years, 48.8% girls), the prevalence of obesity and severe obesity in 2011‐2012 was 21.5% and 6.4%, respectively, compared with 20.2% and 6.0%, respectively, in 2016‐2017. Since 2011‐2012, decreasing trends in obesity and severe obesity (relative declines: 6.0% and 6.3%, respectively, P  < 0.001) have been observed. Significant decreases were observed for all subgroups ( P  < 0.001), although there remained disparities in relative declines over time by race/ethnicity and poverty. Conclusions: Decreasing trends in obesity and severe obesity among all New York City K‐8 public school youth are promising; however, persistent disparities highlight the need to improve intervention design and implementation strategies for groups disproportionately burdened by obesity.